Activity of hammerhead ribozymes containing non-nucleotidic linkers. - Thomson, J B (1993)
Hammerhead ribozymes were synthesized in which the tetranucleotide loop II was replaced by non-nucleotidic linkers of 7, 13, 17 and 19 atoms length. Ribozymes with 17 and 19 atom linkers, in combination with a 4 base pair stem II, had catalytic efficiencies which were 2 fold increased to that of the parent ribozyme with a tetranucleotide loop. Ribozymes with these linkers, but in combination with a 2 base pair stem II, showed a 2 fold decrease in catalytic efficiency when compared to the parent ribozyme. Prolonged preincubation in the presence of MgCl2 was required for hexaethylene glycol linker-modified ribozymes to obtain maximum activity and reproducible kinetic data.